Proceso organizativo, dinámicas comunitarias, sistematización de la información, resistencia territorial, pueblo negro (2021)
The bibliographic compilation takes as reference the organizational processes of struggle and resistance of the black communities of the north of Cauca, with an approach to community dynamics, which, from the conception in the understanding of territorial bets, establishes and marks the traceability of its struggle in the city and the construction of its diverse forms of life, with clear characteristics of Cimarron culture. To that extent, this document made an recognition of the social dynamics of black people; on the care and protection of the ways of live from ancestral knowledge, harmonized by the relationship with their environment, that allows them to establish territorial resistance to care for and protect their ways of life as black people